Recent Progress on Copper-Catalyzed C–C Bond Formation via C(sp2)–H Insertions Using Diazo and Related Compounds - Bera, Satabdi; Jana, Subhenira; Samanta, Rajarshi (Synthesis, 2023)
The site-selective insertion of metal carbenes via C(sp2)–H bond functionalization is an interesting topic within the synthetic chemistry community. In recent years, studies on the formation and applications of copper carbene intermediates have increased significantly due to their cost-effectiveness and versatile reactivities. Furthermore, copper-catalyzed transformations involving C(sp2)–H insertions using diazo and related compounds, along with asymmetric versions, have emerged as new tools for C–C bond formation. This short review summarizes selected recent advances in this field.1 Introduction2 Insertion of Copper Carbenes into Aryl C(sp2)–H Bonds of Arenes3 Copper Carbene Insertion into Aryl C(sp2)–H Bonds of Azaheteroarenes4 Copper Carbene Insertion into C(sp2)–H Bonds of Alkenes5 Conclusions and Perspectives
Keywords: copper catalysis; metal carbenes; C(sp2)–H insertion; C–C bond; diazo compounds